(Phosphinito)aryl benzimidazole PCN pincer palladium(II) complexes: Synthesis, characterization and catalytic activity in CH arylation of azoles with aryl iodides. (15th March 2018) - Wang, Cong; Li, Yang; Lu, Beibei; Hao, Xin-Qi; Gong, Jun-Fang; Song, Mao-Ping
Graphical abstract: Three new PCN pincer Pd(II) complexes with (phosphinito)aryl benzimidazole ligands have been synthesized and well characterized. The pincer Pd complex acted as effective catalyst for the intermolecular arylation of azoles with aryl iodides in the presence of CuI cocatalyst, giving the 2-arylated azoles in generally good to excellent yields. Abstract: The PCN pincer Pd(II) complexes 4a –c with (phosphinito)aryl benzimidazole ligands were conveniently synthesized by one-pot phosphorylation/palladation reaction of a (2-benzimidazolyl)-containing m -phenol derivative 3 . The three complexes were well characterized by spectroscopic methods, elemental analysis and their molecular structures were further determined by X-ray single-crystal diffraction. The Pd(II) center in each complex adopts a typical distorted-square-planar geometry. With a catalyst loading of 0.25–0.5 mol%, complex 4a could effectively catalyze CH arylation of benzothiazole, benzoxazole and thiazole with various aryl iodides in the presence of CuI as a cocatalyst.